Enhancing EFL Learners’ Oral Skills through the Use of BBC Learning English Podcasts as a Home Practice Tool The Case of Second Year Scientific Learners of Abdel Hak Ben Hammouda Secondary School, BBA - Djelloul BRADCHA, Kamel DJENDI (UNIVERSITY OF MOHAMED BOUDIAF, 2021)
Abstract Though there are many studies on the speaking skill and the possible ways to improve it, Algerian secondary school learners are poor when it comes to speaking. Teachers are endeavouring to train their learners to make them confident fluent speakers, which is considered by a lot of people the utmost quest. In addition, huge lacunas have been recorded in the way teachers invest, implement and integrate oral materials within time restrictions set by Algerian ministry of education. Recognising time as a major obstacle on the road towards this honourable purpose, a decision is reached to make use of the time learners spend at home especially during weekends. Therefore, it is hypothesised that using BBC learning English podcasts as a home practice material will enhance Algerian EFL learners’ oral skills significantly. To achieve the objectives of this study, a descriptive method is adopted. It aims to describe two variables: BBC learning English podcasts as an independent variable and the speaking skill as the dependent one. To collect the necessary data, an interview arranged with six secondary school language teachers and a classroom observation took place with second year scientific stream of Abdel Hak Ben Hammouda secondary school. After qualitatively analysing the obtained data, the results showed that the oral skills of the learners under investigation have improved significantly through the use of BBC learning English podcasts as a home practice tool. Finally, the investigators reach, in this research, that BBC learning English podcasts is of paramount importance for enhancing learners speaking skill who are required to practise imitating these recordings for an hour each. This research also recommeds syllabus designers to devise a separate syllabus to improve secondary school learners’ oral skills that should be mainly based on BBC learning English podcast
Keywords: Keywords: EFL Learners.Oral .Learning